Simultaneous energy storage and recovery in triplex-tube heat exchanger using multiple phase change materials with nanoparticles. (May 2022) - Mozafari, M.; Lee, Ann; Cheng, Shaokoon
Highlights: Integrating PCMs with different melting points improves the performance of TTHX. Natural convection in the lower half of TTHX is improved by incorporating 2 PCMs. System's initial condition is crucial for thermal energy storage design under SCD. 3 NEPCMs arranged in radial direction produces the best system's performances. Nanoparticles dramatically improve the melting and solidification of PCMs. Abstract: This study investigates the thermal response of triplex-tube heat exchanger (TTHX) systems and their simultaneous storage and recovery qualities using novel designs with multiple-phase change materials (PCM s). Specifically, the effects of nanoparticles and different PCM design configurations are studied. A numerical model that includes the Brownian motion of nanoparticles, and the convection motion of liquid PCM, is developed and first validated, with results showing close correspondence and outcome to those obtained from physical experiments. Results from this study demonstrate that the lower region of the horizontal TTHX shows weak natural convection that can be effectively improved when multiple PCMs are applied, resulting in a significantly improved uniform convection in both the lower and upper regions of the TTHX. Stored latent energy is analyzed for different cases, and results show that using two or more PCMs can significantly increase the stored latent energy by at least 40%, after 1 h This study also shows that the thermal response of a TTHX may be dramatically improved when 5% of aluminium oxide (Al₂O₃) nanoparticles are added to the PCMs. The design with 3 PCMs and with the integration of nanoparticles demonstrates the fastest thermal responses for the fully melted and fully solidified initial conditions. Additionally, the time-averaged values of heat storage and recovery enhancement ratios are found to be 68.95%, and 50.33%, respectively. Depending on the initial temperature of the system, applying multiple PCMs with nanoparticles can accelerate the energy storage and recovery times by up 2.25 and 5.57 times compared to the baseline case (1 PCM without nanoparticles), highlighting the benefits of improving performances of TTHX using multiple PCMs with nanoparticles.